The impact of HIV-1 subtypes on virologic and immunologic treatment outcomes at the Lagos University Teaching Hospital: A longitudinal evaluation - Ogbenna, Ann Abiola (PLoS One, 2020)
INTRODUCTION: HIV is a highly diverse virus with significant genetic variability which may confer biologic differences that could impact on treatment outcomes. MATERIALS AND METHODS: We studied the association between HIV subtypes and immunologic and virologic outcomes in a longitudinal cohort of 169 patients on combination antiretroviral therapy. Participants were followed up for 5 years. Demographic data, CD4 cell count and viral loads (VL) were extracted from medical records. Whole protease gene and codon 1–300 of the reverse transcriptase gene were sequenced and analysed. RESULTS: Sixty-four percent of participants were females with a median age of 35 years. Twelve different subtypes were observed, the commonest being CRF 02_AG (55.0%) and subtypes G (23.1%). All subtypes showed steady rise in CD4 count and there was no difference in proportion who achieved CD4+ cell count rise of ≥100 cells/μL from baseline within 12 months’ post-initiation of ART, or ≥350 cells/μL at 60 months’ post-initiation. Median time to attaining a rise of ≥350 cells/μL was 24 months (6–48 months). The proportion that achieved undetectable VL at month 6 and 12 post-initiation of ART were comparable across subtypes. At end of 5(th) year, there was no statistical difference in proportion with virologic failure. CONCLUSION: No association between HIV subtypes and immunologic or virologic response to therapy was observed, suggesting that current first-line ART may have similar efficacy across subtype predominating in South-West Nigeria.